2008
DOI: 10.2528/pier08010303
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Propagation of Em Pulse Through Lossless Non-Uniform Dielectric Slab Using Characteristic-Based Method

Abstract: Abstract-This paper demonstrates the one-dimensional computational results of the propagation of Gaussian electromagnetic pulse through dielectric slabs of finite thickness with variation in permittivity. The numerical approach used is the characteristic-based method solving the time-domain Maxwell curl equations involved with nonuniform permittivity. In the numerical model, all dielectric slabs are assumed to be isotropic, lossless, and linear. The permittivity of dielectric slab may increase or decrease line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…It is shown that MOC yields results which are compatible with data generated by the FDTD technique [11] and in good agreement with the theoretical values when EM fields reflected from a traveling and/or vibrating perfect surface [12]. Also, MOC produces reasonable trends in the following cases: the effects of medium conductivity on the propagation of EM pulse onto conducting dielectric half space [13] and the propagation of EM pulse through lossless non-uniform dielectric slab [14].…”
Section: Introductionsupporting
confidence: 68%
“…It is shown that MOC yields results which are compatible with data generated by the FDTD technique [11] and in good agreement with the theoretical values when EM fields reflected from a traveling and/or vibrating perfect surface [12]. Also, MOC produces reasonable trends in the following cases: the effects of medium conductivity on the propagation of EM pulse onto conducting dielectric half space [13] and the propagation of EM pulse through lossless non-uniform dielectric slab [14].…”
Section: Introductionsupporting
confidence: 68%
“…is both complex and time-consuming. From one hand, the non-homogenous structure and from the other hand, the high frequency of applications, demand high density meshing in order to achieve accurate response [1][2][3].…”
Section: Abstract-the Development Of Numerical Techniques Enables Us Tomentioning
confidence: 99%
“…is both complex and time-consuming. From one hand, the non-homogenous structure and from the other hand, the high frequency of applications, demand high density meshing in order to achieve accurate response [1][2][3].The explained method in this paper enables us to design a Chebyshev band passes filter by coaxially placing high-Q TM 01δ dielectric resonators in a cutoff circular waveguide. In the presented work, discussions are made regarding high-Q resonators and interresonator coupling.…”
mentioning
confidence: 99%
“…In [13], the perfect surface travels at extremely high velocity, 90% of the speed of light. Computational results generated by MOC were found to give reasonable trends in the following cases: the effects of medium conductivity on the EM fields propagating onto conducting dielectric half space [14] and the transmission of EM pulse through lossless non-uniform dielectric slab [15]. To overcome the grid distortion caused by the rotating cylinder, PCSBG was proposed based on the nature of MOC that all field components are defined at the cell center [16].…”
Section: Introductionmentioning
confidence: 99%